Peningkatan Keterampilan Sosial Peserta Didik melalui Model Project Based Learning (PjBL) dalam Pembelajaran IPAS Kelas V SDIT Nur Hidayah - Anggun Kusuma; Ani Purwanti; Anni’mah Nurul; Siti Istiyati; Sri Lestari (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2025)
Education is a right that must be granted to all individuals in order to develop their potential in both spiritual and social aspects of life. While intelligence is the main focus of education, social skills must also be instilled and taught to students. The social skills of elementary school students are generally still underdeveloped, as students at this stage tend to be egocentric. One solution to improve students' social skills is by implementing project-based learning (PjBL) in the IPAS subject. Learning and social skills in IPAS instruction need to be applied to provide concrete learning experiences based on the students’ understanding of the concepts taught. This classroom action research was conducted with the aim of improving the social skills of fifth-grade students at SDIT Nur Hidayah through learning activities using the PjBL model. The data collection technique used was observation. The data were analyzed using descriptive analysis across three phases: pre-cycle, cycle 1, and cycle 2. The results of this study show an increase in students’ social skills, with an average score of 67 in the pre-cycle, 78 in cycle 1, and 90 in cycle 2. These findings indicate that the implementation of project-based learning (PjBL) is effective in enhancing the social skills of fifth-grade students at SDIT Nur Hidayah.